Sistem Pendukung Keputusan Pemilihan Smartphone Bekas Menerapkan Metode SAW - Frendiza Nawandi; Azzam Muzhaffar; Muhammad Ramadhika Putra Tamtomo; Resad Setyadi (Journal of Information System Research (JOSH), 2023)
The selection of used Smartphones made by buyers sometimes confuses prospective buyers of what used Smartphones to buy according to the desired criteria. Based on this, in this study a decision support system was built that was used to carry out the process of selecting used smartphones that matched the criteria, namely price, camera, RAM, internal memory, processor, battery, and weight. The decision-making method used is the Simple Additive Weighting (SAW) method. This method is used to determine the weight value of each criterion, which is then carried out a ranking process to determine alternative used Smartphones. The results of this study are to explain the results of the stages of calculating the alternative value criteria in the implementation of the Program which has been carried out based on manual calculations and explaining that the calculation can produce the final stage where the alternative smartphone used MI 10t Pro has a ranking number 1 and has the same value as manual calculations, namely 91.1. With a decision support system that uses the SAW method, (Simple Additive Weighting), it can help consumers choose used cellphones based on predetermined criteria.